2016
DOI: 10.1016/j.palaeo.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach for identifying plant ecogroups in the Romanian Early Jurassic terrestrial vegetation

Abstract: Community level ecology is considered to support significantly the recognition of the ecological status of plant taxa and the identification of plant ecogroups, thus it generally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…The joint distribution of the species along the orthogonal axes of PCA analysis may give a rough estimation of their ecological profiles. This method is commonly used in palaeobotany since Spicer andHill used it in 1979 (Spicer andHill 1979) and gave a good results in the palaeoecological analysis of Jurassic flora from Mecsek (Barbacka et al 2016). The effectiveness depends on the original correlation values among the variables.…”
Section: Geology Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The joint distribution of the species along the orthogonal axes of PCA analysis may give a rough estimation of their ecological profiles. This method is commonly used in palaeobotany since Spicer andHill used it in 1979 (Spicer andHill 1979) and gave a good results in the palaeoecological analysis of Jurassic flora from Mecsek (Barbacka et al 2016). The effectiveness depends on the original correlation values among the variables.…”
Section: Geology Materials and Methodsmentioning
confidence: 99%
“…C. denticulata was the most important fern in coal layers in Romania. It colonized areas in the closing stages of the mire development together with T. brauniana and D. nilssoniii or formed monospecific assemblages (Van Konijnenburg- van Cittert 2002;Popa 1997Popa , 1998Popa , 2000Popa , 2014Popa and Meller 2009;Barbacka 2011;Barbacka et al 2015Barbacka et al , 2016. However, the Hungarian plant remains were found in all rock types except channel fill deposits, indicating that the habitat of C. denticulata extended towards dry and moderately disturbed conditions with a high environmental tolerance Barbacka 2011;Bodor and Barbacka 2012).…”
Section: Suggested Environmental Requirements Of the Fernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative taxonomy has improved the original descriptive qualitative taxonomy to a precise quantitative level, and this has been matured into the study of the classification relationship of extant plants (Yang Hanbi and Xu Kexue, 1983;Liu Xingdong and Cen Qingya, 1996;Zhen Yanchao, 2012;Li Chao et al, 2013;Shen Xuemei, 2015;Wu Baohuan et al, 2018;Yang Li'e et al, 2017;Lu Guoquan and Peng Lin, 2018). However, this method has been usually used to explain the floristic regions of fossil plant flora in palaeobotany (Mi Jia Rong et al, 1986;Sun Fusheng, 1989;Wang Jun et al, 1999;Liu Yan and Li Lu, 2006;He Yingfu, 2007;Li Qijia, 2016), but it is rarely used in the classification of fossil plants (Xu Hanqiu, 1988;Mi Jia Rong et al, 1991;Lv Xiaodong, 2010;Barbacka et al, 2016). Furthermore, the related studies on the quantitative analysis of the Dicksoniaceae fossils have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Such a coal genesis mechanism was described by Popa (1998Popa ( , 2014 for European and Greenlandic Triassic and Jurassic coals, with primary coal generators such as sphenopsids and conifers, and secondary coal generators represented by a ternary association between a fern, a bennettitalean and a ginkgoalean representative, also called by Popa (2014) as a ternary rule. This ternary rule was later demonstrated statistically by Barbacka et al (2016). Now it can be demonstrated that during the Cenozoic times, Ponephrium stiriacum played the same role as a secondary coal generator, the same way a fern representative played during the Jurassic within its ternary association.…”
Section: Discussionmentioning
confidence: 84%